2017
DOI: 10.1159/000468368
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Enriched Environment Reduces Neuronal Apoptosis in the Periinfarct Cortex after Cerebral Ischemia/Reperfusion Injury

Abstract: Background/Aims: Enriched environment (EE) has been reported to exert neuroprotective effect in animal models of ischemic stroke. However, the underlying mechanism remains unclear. The purpose of this study was to investigate the effect of EE treatment on neuronal apoptosis in the periinfarct cortex after cerebral ischemia/reperfusion (I/R) injury. Methods: The cerebral I/R injury was established by middle cerebral artery occlusion (MCAO). A set of behavioral tests including the modified neurological severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Since apoptosis and autophagy are now relatively well defined mechanisms of stroke mediated brain injury [25,26], readily available compounds that are able to combat these pathways are desirable subjects of further studies to develop therapeutic strategies to treat stroke patients. In this study, we subjected rats to transient MCAO and studied the effects of bilobalide in post MCAO recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Since apoptosis and autophagy are now relatively well defined mechanisms of stroke mediated brain injury [25,26], readily available compounds that are able to combat these pathways are desirable subjects of further studies to develop therapeutic strategies to treat stroke patients. In this study, we subjected rats to transient MCAO and studied the effects of bilobalide in post MCAO recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, Bax and Bak are processed and inserted into the mitochondrial membrane to release downstream pro-apoptotic proteins such as cytochrome c, Smac/Diablo, HTRA2/Omi, apoptosis-inducing factor, and endonuclease G. Cytochrome c binds apoptotic protease activating factor 1 (APAF-1) to activate pro-caspase-9 to form the apoptosome. The apoptosome induces a caspase cascade to promote apoptosis via activation of caspase-9 [86]. Endo G also interacts with AIF to cause DNA fragmentation.…”
Section: Apoptosis and Mitoptosismentioning
confidence: 99%
“…[6][7][8][9][10] Most studies have indicated that cell apoptosis plays a vital role in the mechanisms underlying I/R-induced neuronal damage. 11 Therefore, inhibiting apoptosis may be a promising direction for neuroprotection in I/R injury.…”
Section: Introductionmentioning
confidence: 99%